(untitled) (Research, Society and Development, 2021)
The study aimed to identify the legal-institutional configuration and the decision-making process in the management of Participatory or Environmental Deliberative Institutions in the territory of the citizenship of the Middle Sertão-PB, seeking to point out participatory management actions in / in making sustainable environmental decisions. To answer the objective in this research, we used the qualitative method, in addition to descriptive, documentary and field research. As a result, it was observed that the councils analyzed have a large part of their functionality focused on the development of the Program, with little occurrence of speeches related to the impacts on agriculture, the production chain and sustainability. Its existence, in a greater number of municipalities, may be linked to financial issues (transfer and inspection of transfer of resources), which differs from Councils with an environmental theme, which have little presence of municipalities in the territory, as they do not deal directly with policies that have financial transfers or because the implementation of public policies is not linked to their existence. Among the issues related to the decision-making process, it can be highlighted that most decisions are related to administrative and bureaucratic issues that concern public management itself.